SUSTAINABILITY AND EFFICIENCY IN GRAIN PRODUCTION: A CRITICAL ANALYSIS OF INDUSTRY ROLE AND IMPACT - Dildora A. Kurbanova (European Science Publishing, 2024)
This paper examines the complex relationship between sustainability and efficiency in global grain production systems and their role in the food industry. Through analysis of theoretical foundations and current practices, we investigate the evolution of sustainability concepts, efficiency measures, and their practical applications in modern grain production. The research demonstrates that sustainability encompasses interconnected ecological, social, and economic dimensions that must be balanced for effective implementation in the agricultural sector.
Keywords: Industry, grain production, critical analysis.